2022
DOI: 10.1002/lno.12258
|View full text |Cite
|
Sign up to set email alerts
|

Sediment organic carbon stocks were similar among four species compositions in a tropical seagrass meadow

Abstract: Seagrass meadows composed of larger species are assumed to store larger sediment organic carbon (Corg) stocks, storing more Corg in their tissues and larger leaves promoting greater burial of seagrass and non‐seagrass Corg. However, the influence of species composition on sediment Corg stocks remains poorly understood mainly from challenges in isolating it from confounding factors. We assessed Corg stocks in seagrass biomass and sediment of four species compositions in a tropical Caribbean meadow. We hypothesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…Several studies in this special issue address the origin, variability, and drivers of the sediment carbon pool and fluxes. Samper-Villarreal et al (2022) found that sediment organic carbon storage in tropical seagrass meadows can be independent of species composition, while Kammann et al (2022) demonstrated that vegetation traits and nutrient availability modify organic carbon sequestration in other seagrass and mangrove sediments. Krause et al (2022) showed that a large fraction of sediment organic carbon in seagrass and saltmarsh ecosystems originates from adjacent ecosystems rather than through in situ production.…”
mentioning
confidence: 99%
“…Several studies in this special issue address the origin, variability, and drivers of the sediment carbon pool and fluxes. Samper-Villarreal et al (2022) found that sediment organic carbon storage in tropical seagrass meadows can be independent of species composition, while Kammann et al (2022) demonstrated that vegetation traits and nutrient availability modify organic carbon sequestration in other seagrass and mangrove sediments. Krause et al (2022) showed that a large fraction of sediment organic carbon in seagrass and saltmarsh ecosystems originates from adjacent ecosystems rather than through in situ production.…”
mentioning
confidence: 99%